Cognitive behaviour therapy in medication-treated adults with ADHD and persistent Symptoms: A randomized controlled trial - Einarsson Emil (BMC Psychiatry, 2011)
Abstract Background Attention deficit hyperactivity disorder (ADHD) in adulthood is not fully treated by psychopharmacological treatment alone. The main aim of the current study was to evaluate a newly developed cognitive behaviour therapy (CBT) based group programme, the Reasoning and Rehabilitation for ADHD Youths and Adults (R&R2ADHD), using a randomized controlled trial. Methods 54 adults with ADHD already receiving psychopharmacological treatment were randomly allocated to an experimental (CBT/MED) treatment condition (n = 27) and a 'treatment as usual' (TAU/MED) control condition (n = 27) that did not receive the CBT intervention. The outcome measures were obtained before treatment (baseline), after treatment and at three month follow-up and included ADHD symptoms and impairments rated by independent assessors, self-reported current ADHD symptoms, and comorbid problems. Results The findings suggested medium to large treatment effects for ADHD symptoms, which increased further at three month follow-up. Additionally, comorbid problems also improved at follow-up with large effect sizes. Conclusions The findings give support for the effectiveness of R&R2ADHD in reducing ADHD symptoms and comorbid problems, an improving functions associated with impairment. The implications are that the benefits of R&R2ADHD are multifaceted and that combined psychopharmacological and CBT based treatments may add to and improve pharmacological interventions. Trial registration ACTRN12611000533998 (http://www.ANZCTR.org.au/ACTRN12611000533998.aspx)